Autonomic dysfunction as the initial presentation in spinocerebellar ataxia type 3: A case report and review of the literature - Jin, Yi; Chen, Yuchao; Li, Dan; Qiu, Mengqiu; Zhou, Menglu; Hu, Zhouyao; Cai, Qiusi; Weng, Xulin; Lu, Xiaodong; Wu, Bin (Frontiers in Neurology, 2022)
Spinocerebellar ataxia type 3 (SCA3), as the most frequent autosomal dominant ataxia worldwide, is characterized by progressive cerebellar ataxia, dysarthria and extrapyramidal signs. Additionally, autonomic dysfunction, as a common clinical symptom, present in the later stage of SCA3. Here, we report a 44-year-old male patient with early feature of autonomic dysfunction includes hyperhidrosis and sexual dysfunction , followed by mild ataxia symptoms. The Unified Multiple System Atrophy Rating Scale (UMSARS) indicated significant dysautonomia during autonomic function testing. Combination of early and autonomic abnormalities and ataxia would be more characteristic of the cerebellar type of multiple system atrophy (MSA-C), the patient's positive family history and identification of an ATXN3 gene mutation supported SCA3 diagnosis. To best of our knowledge, the feature as the initial presentation in SCA3 has not been described. Our study demonstrated that autonomic dysfunction may have occurred during the early stages of SCA3 disease.